Measurement of the CKM angle γ in B ± → DK ± and B ± → Dπ ± decays with D → K S 0 $$ K_{S}^0 $$ h + h − - The LHCb collaboration; R. Aaij; C. Abellán Beteta; T. Ackernley; B. Adeva; M. Adinolfi; H. Afsharnia; C. A. Aidala; S. Aiola; Z. Ajaltouni; S. Akar; J. Albrecht; et al. (Journal of High Energy Physics, 2021)
Abstract A measurement of CP-violating observables is performed using the decays B ± → DK ± and B ± → Dπ ±, where the D meson is reconstructed in one of the self-conjugate three-body final states K S 0 $$ K_{S}^0 $$ π + π − and K S 0 $$ K_{S}^0 $$ K + K − (commonly denoted K S 0 $$ K_{S}^0 $$ h + h − ). The decays are analysed in bins of the D-decay phase space, leading to a measurement that is independent of the modelling of the D-decay amplitude. The observables are inter- preted in terms of the CKM angle γ. Using a data sample corresponding to an integrated luminosity of 9 fb −1 collected in proton-proton collisions at centre-of mass energies of 7, 8, and 13 TeV with the LHCb experiment, γ is measured to be 68.7 − 5.1 + 5.2 ° $$ \left({68.7}_{-5.1}^{+5.2}\right){}^{°} $$ . The hadronic parameters r B DK , r B Dπ , δ B DK , and δ B Dπ $$ {r}_B^{D K},{r}_B^{Dπ},δ_B^{D K},\kern0.5em and\kern0.5em δ_B^{Dπ} $$ , which are the ratios and strong-phase differences of the suppressed and favoured B ± decays, are also reported.